2018
DOI: 10.5812/zjrms.67003
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of In vitro Efficacy of Marrubium vulgare L. Essential Oil and Extracts Against Trichomonas vaginalis

Abstract: Background: Trichomoniasis is one of the most common nonviral sexually transmitted infections worldwide that its drug-resistant cases are on the rise. Objectives: The aim of this study was to evaluate the antiprotozoal activity of Marrubium vulgare essential oil and extracts against Trichomonas vaginalis. Methods: After preparation of essential oil and extracts of M. vulgare, five T. vaginalis isolates were subjected to susceptibility testing after 24 and 48 hours of incubation at 35.5°C under aerobic conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…To this end, plant-based products are of great interest for the treatment of T. vaginalis and other parasites attributed to relatively similar therapeutic proficiency and high safety profile. Up to now, a limited number of essential oils have been tested in vitro on T.vaginalis, including [44,[54][55][56][57][58]. Among them, Ocimum basilicum shows one of the most efficient antitrichomonas activity, with 100% inhibition of of parasitic growth at a concentration of 30 mg/ml after 24 h of incubation [59].In the present work,the authors demonstrated that essential oil of A. sessiflora display a very good inhibitory effect on T. vaginalis, with IC50 value of 0.016% (v/v) after 48 hours, corresponding to 120 µg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, plant-based products are of great interest for the treatment of T. vaginalis and other parasites attributed to relatively similar therapeutic proficiency and high safety profile. Up to now, a limited number of essential oils have been tested in vitro on T.vaginalis, including [44,[54][55][56][57][58]. Among them, Ocimum basilicum shows one of the most efficient antitrichomonas activity, with 100% inhibition of of parasitic growth at a concentration of 30 mg/ml after 24 h of incubation [59].In the present work,the authors demonstrated that essential oil of A. sessiflora display a very good inhibitory effect on T. vaginalis, with IC50 value of 0.016% (v/v) after 48 hours, corresponding to 120 µg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…The biological activities of essential oils, mainly focused on the antibacterial, antifungal and antioxidant activities [1,3]. Only a few essential oils, especially some species of the Lamiaceae family, have been investigated against Trichomonas [47][48][49][50][51]. Notably, our work on the antitrichomonas activity of L. domatiophorus oil, for the first time, demonstrated an effective inhibition against T. vaginalis.…”
Section: Antiviral Activitymentioning
confidence: 88%
“…However, the emergence of resistance has limited the effectiveness of this therapy [34,35]. Therefore, it is of critical importance to search for novel pharmaceutical alternatives to treat trichomoniasis successfully in clinical settings [36]. Only a few essential oils, especially some species of the Lamiaceae family, have been investigated against Trichomonas [32,[36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is of critical importance to search for novel pharmaceutical alternatives to treat trichomoniasis successfully in clinical settings [36]. Only a few essential oils, especially some species of the Lamiaceae family, have been investigated against Trichomonas [32,[36][37][38][39]. Particularly, the essential oil of Marrubium vulgare displayed antitrichomonas activity with an average MIC value of 291 ± 136 µg/mL after 48 h of incubation [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation